2020
DOI: 10.3174/ajnr.a6559
|View full text |Cite
|
Sign up to set email alerts
|

Fast Stent Retrieval Improves Recanalization Rates of Thrombectomy: Experimental Study on Different Thrombi

Abstract: BACKGROUND AND PURPOSE: About 20% of patients with acute ischemic stroke due to large-artery occlusion do not achieve recanalization with mechanical thrombectomy. We aimed to determine whether the speed of retrieval of the stent retriever influences the efficacy in removing different clot types.MATERIALS AND METHODS: Sixty mechanical thrombectomies were performed using an in vitro pulsatile cerebrovascular circulation model with controlled pressure and flow rate. Experiments were dichotomized into fast and slo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
(38 reference statements)
1
9
0
Order By: Relevance
“…5 Moreover, in an in vitro model, when one used a fast retrieval, the extraction of fibrin-rich clots was 4 times greater. 10 This result was confirmed by our in vivo study in which reaching a complete first-pass recanalization (first-pass effect) was 4 times greater with a fast retrieval. Although a first-pass effect is infrequently obtained (20%-35% of patients), it is associated with improved clinical outcome, reduced adverse effects, and decreased mortality.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…5 Moreover, in an in vitro model, when one used a fast retrieval, the extraction of fibrin-rich clots was 4 times greater. 10 This result was confirmed by our in vivo study in which reaching a complete first-pass recanalization (first-pass effect) was 4 times greater with a fast retrieval. Although a first-pass effect is infrequently obtained (20%-35% of patients), it is associated with improved clinical outcome, reduced adverse effects, and decreased mortality.…”
Section: Discussionsupporting
confidence: 69%
“…A fast retrieval may mobilize the clot suddenly, enhance clot wedging, and minimize loss of apposition during retrieval. 10 The present study aimed to evaluate whether stent-retrieval speed influences recanalization rates and clinical outcome in patients presenting with negative SVS clots.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…37 However, Soize et al found an improvement in recanalization rates using fast compared to slow retrieval. 115 Fast retrieval quickly mobilized the clot which allowed for a higher pulling force. While fast retrieval seems promising in terms of recanalization, perforating arteries cannot be modelled accurately, and the likelihood of damage remains unclear.…”
Section: Novel Imaging and Endovascular Approachesmentioning
confidence: 99%
“…White clots present with lower attenuation on non-contrast-enhanced CT and increased resistance to both intravenous lysis and mechanical thrombectomy [23]. Technical aspects of MT such as speed retrieval [24] or device selection [15] may be improved based on clot composition [20,23,25]. Namely utilization of stent retriever in MT seems to be less effective in the case of calcified thromboemboli [26].…”
Section: Plos Onementioning
confidence: 99%